Disasters and journalism: the report, settings, interactions and practical and psychological needs of all implicated - Rodríguez, Pepe; Odriozola Farré, Begoña (Estudios sobre el Mensaje Periodístico, 2012)
This paper analyzes critically the construction of journalistic report of disaster, explains the basic operating structure in emergency settings beside interactions and practical and psychological needs of all involved, emphasizing those that concern victims and journalists. The analysis reviews the specialized literature and is founded on the experience accumulated by the authors, since 2005, on the intervention teams in the Medical Emergency System of Catalonia and the professional exchange with other state emergency teams. The psychosocial problems that inappropriate media coverage may cause to the victims are analyzed, especially victimization and secondary traumatization, and also the lack of professional and self-protection training of journalists covering these events and posttraumatic stress problems that they may suffer.
Keywords: journalism; disaster; victim; trauma; posttraumatic stress.